PENGARUH DIMENSI KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KARTU SELULER SIMPATI DI KOTA KENDARI - Heriyanto Heriyanto; Patwayati Patwayati; Nasrul Nasrul; Isalman Isalman; Farhan Ramdhani Istianandar (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2023)
This study aims to determine both simultaneously and partially the effect of dimensions and product quality on the purchase of a simpathy cellular card in Kendari city. The population in this study is Kendari city residents who buy sympathy cards. Due to the infinite number of population, the determination of the sample used is accidental sampling. The data collection method in this study was to use a questionnaire. This study uses multiple linear regression analysis. The results showed that simultaneously and partially product quality and dimensions had a positive and significant effect on the purchase of a Simpati cellular card in the city of Kendari. That is, if the dimensions and quality of the product are good, it will tend to influence purchases